Culture and society in tourism contexts - Nogués-Pedregal, A. M. (Tourism social science series ;, 2012)
This book strives to understand the social and cultural dynamics in Mediterranean tourist destinations through ethnographic examples from Greece, Spain, Egypt, France, Malta and Crete. Migrants, tourists and new residents with different nationalities and personal motivations converge and share with locals in the same locations and/or create new places that mushroom all over the territories (i.e. urbanisations in the coasts). As this occurs the practices and meanings that give sense to daily life seem to blur traditional dichotomic notions such as leisure and labour, residents or locals, nationals or foreigners. The work of several social scientists, from varied backgrounds, over numerous years, using multiple research techniques to observe cultures and societies as they occur in daily practices is documented here. This book underlines the importance of focusing on the relations among the relations, that is, not simply looking at only one of the possible social pairs among these groups (i.e. tourists-locals; tourist-new residents etc.) but at how the presence of all the groups affect both the whole social and cultural processes and the relations among them.